Symposium 2: Ubiquitous Transformations - Haythornthwaite, Caroline (Proceedings of the International Conference on Networked Learning, 2008)
Internet-based trends that emphasize contribution, conversation, participation, and community exercise a significant impact on learning. They bring changes in where we find information, who we learn from, how learning progresses, and how we contribute to our learning and the learning of others. This paper addresses two aspects of participatory transformations arising from ubiquitous, networked learning: the invisible work of networked learners, and the changing nature of networked learning relationships. While much attention is given to the unlimited possibilities for retrieving from online sources, little addresses the limits to such sources or the work that devolves to the learner for critical evaluation of retrieved information. Distributed practices entail a redistribution of processes and responsibilities to individuals who then perform the invisible work of networked learning. An autonomous learner is responsible for, and in many cases alone, in creating their own learning context and content as they search the internet for materials to support their needs. Such distribution of responsibilities increases the need for individuals to attain a variety of media literacy skills, including social skills in online participation and critical evaluation skills to use to evaluate retrieved content and retrieval techniques. Critical attention is also needed for the impact of ubiquitous contribution and retrieval afforded by the Internet, including whose information content predominates on the net, and whose is most likely to be retrieved by common retrieval techniques (e.g., through popularity rankings). This raises the need for not only critical media literacy, but also critical retrieval and retrieval technology literacy. Distribution is also realigning of network roles and relations. Experts in the form of information professionals and teachers are bypassed in the expedience and convenience of retrieval and learning from the web. Peers and other learners become information sources and teachers. Emergent changes in relationships that affect educational settings include changes in authorial relationships with leaders, instructors and documentary sources, peer relationships with other learners (both contemporary and past), and relationships with local communities and networks. This paper explores these changes in roles and relations addressing questions such as: What is expertise in the age of participatory learning, and whose definition is it anyway? In an age of participatory culture, and participatory learning, what are the roles of learners and teachers? What are the practices required of each? How will the persistent record left by so much online participation be used? What is the worth of a publisher’s or journal name in the age of wikipedia? What does local mean in the age of online learning? And, What is the role of local in online learning?